Conference report: International conference “Language, Culture and Law – Semiotic Perspectives on Forestry & Hunting «Cultural Value of Hunting». 18th Conference on Translation, Interpreting, LSPs and Cultural Studies”. Obrzycko, 15th–17th June 2023 - Nowak, Oliver (Glottodidactica, 2023)
Conference report: International conference “Language, Culture and Law – Semiotic Perspectives on Forestry & Hunting «Cultural Value of Hunting». 18th Conference on Translation, Interpreting, LSPs and Cultural Studies”. Obrzycko, 15th–17th June 2023